The four elements of success a simple personality profile that will transform your team - Jones, Laurie Beth (Nelson Business, 2005)
Laurie Beth Jones, management expert and business consultant extraordinaire, noticed that none of the personality/temperament profiles in the market today, none of them provided a tool that was simple, visual, intuitive, and powerful enough to create a shift in thinking as well as relating. So she developed The Path Elements Profile (PEP), which can be used in recruitment, placement, retention, team building, and customer relations as businesses transform many individuals into a harmonizing, humming force for good. Within the framework of the book will be scriptural examples as well as modern day business stories.